Optical method to determine in vivo capillary hematocrit, hemoglobin concentration, and 3‐D network geometry in skeletal muscle. (22nd February 2022) - Christie, Jaryd R.; Kong, Isaac; Mawdsley, Laura; Milkovich, Stephanie; Doornekamp, Ande; Baek, Jason; Fraser, Graham M.; Ellis, Christopher G.; Sové, Richard J.
Abstract: Objective: The aim of this study was to develop a tool to visualize and quantify hemodynamic information, such as hemoglobin concentration and hematocrit, within microvascular networks recorded in vivo using intravital video microscopy. Additionally, we aimed to facilitate the 3‐D reconstruction of the microvascular networks. Methods: Digital images taken from an intravital video microscopy preparation of the extensor digitorum longus muscle in rats for 25 capillary segments were used. The developed algorithm was used to delineate capillaries of interest, calculate the optical density for each pixel in the image, and reconstruct the 3‐D capillary geometry using the calculated light path‐lengths. Subsequently, the mean corpuscular hemoglobin concentration (MCHC), hemoglobin concentration, and hematocrit for these capillaries were calculated. We evaluated the hematocrit values determined by our methodology by comparing them to those obtained using a previously published method. Results: The hematocrit values from the proposed optical method were strongly correlated with those calculated using published methods r 2 (25) = .92, p  < .001, and demonstrated excellent agreement with a mean difference of 1.3% and a coefficient of variation (CV) of 11%. The average MCHC, hemoglobin concentration, and light path‐lengths were 23.83 g/dl, 8.06 g/dl, and 3.92 µm, respectively. Conclusion: The proposed methodology can quantify hemodynamic measurements and produce functional images for visualization of the microcirculation in vivo.